Rapid Appraisal of Manas Tiger Reserve to understand its Conservation Challenges - Awadhiya, Ankur; Srivastava, Ajay (Indian Forester, 2018)
The authors present an analysis of the prevalent conservation challenges in Manas Tiger Reserve and World Heritage Site, together with the Transboundary Conservation Area, as discerned utilising four distinct techniques: literature survey, field visits, participatory appraisal of key stakeholders and focussed interviews. They found significant differences in the challenge perceptions of different stakeholders, indicating not only availability heuristic in operation, but also the complimentary strategies that need to be deployed for an ameliorated participatory management. They believe that the information presented through this analysis will be found useful by the managers for an expeditious mitigation of these conservation challenges, so obligatory for the management of this exceptional biodiversity hotspot.